Early morning - Pigdon, Keith (Cleveland, Toronto : Modern Curriculum Press, 1987)
You have probably noticed how we tend to do different things at different times of the day. This book shows how people and animals do all kinds of things early in the morning.
Keywords: Work--Fiction; Children stories